The Evaluation of The Achievements of Universal Health Coverage Program in Health Facilities in Gresik District - Widiharti; Diah Ratnasari; Endah Mulyani; Wiwik Widiyawati; Kholifah, Anik Nur; Indarto, Tomi (STIKes Patria Husada Blitar, 2024)
Quality and affordable health services are a government obligation that must be provided to every citizen. Universal Health Coverage (UHC) refers to a health care system that provides quality health care coverage and financial protection to all citizens. In implementing UHC there are various challenges that can hinder the achievement of UHC, especially in Gresik Regency. This research aimed to provide results on the achievement value of the UHC program in Gresik Regency. The type of the research was a mix method, namely a mixture of qualitative and quantitative types of research. The research was carried out at first-level government facilities, namely 32 Community Health Centers in Gresik Regency. The assessment of UHC data in this research was based on several indicators, namely membership, basic service coverage and UHC utilization. The research results showed (1) Total JKN membership meets the Great category (2) JKN membership was based on the membership segment of the majority of APBN Contribution Assistance Recipients (3) UHC basic service coverage was based on (a) Maternal & Child Health Dimensions, the majority was in the good category (b) The majority of Infectious Diseases Dimensions good category (c) The majority of Non-Communicable Diseases dimensions were in the poor category (d) The majority of the dimensions of Capacity & Access to Health Services were in the good category